Differences in muscle oxygenation between young and middle-aged recreationally active men during high-volume resistance exercise - Gepner, Yftach (Array, 2019)
The aim of this study was to compare muscle oxygenation of the vastus lateralis during a high-volume isokinetic resistance exercise protocol (HVP) between young adult (YA) and middle-aged adult (MA) men. Twenty recreationally trained men were assigned to either the YA (age 21.8±2.0 years, body mass 90.7±11.6 kg, body height 179±4.7 cm) or MA (age 47.0±4.4 years, body mass 96.1±21.6 kg, body height 177±7.7 cm) group. The HVP consisted of eight sets of 10 repetitions of unilateral isokinetic concentric knee extension and eccentric knee flexion at 60°·s-1. Changes in tissue hemoglobin saturation index (TSI), tissue oxygenated hemoglobin concentration (O2Hb), deoxygenated hemoglobin (HHb), and muscle oxidation index (O2Hb-HHb) were measured during the exercise session using the near-infrared spectroscopy (NIRS). Data were analyzed using two-way mix factorial analyses of variance. Prior to exercise, TSI was significantly greater (p=.024) for YA compared to MA. Significant decreases in O2Hb and O2Hb-HHb and increases in HHb were observed during each of the eight sets relative to the rest periods (p<.05) for both groups. The average change during the eight sets of the HVP revealed a significantly higher (p=.036) level of HHb and a lower (p=.029) level of O2Hb-HHb for MA compared to YA. A significant negative correlation was also noted at baseline between O2Hb-HHb index and the cross-sectional area of the vastus lateralis muscle (r=-.45, p=.045). During a high- volume resistance exercise, MA experienced reduced muscle oxygen saturation levels compared to YA. These results may be attributed to reductions in local tissue oxidative capacity and reduced blood delivery occurring during middle-age, and possibly due to group differences in muscle morphology.